Analisis Kebangkrutan PT. ASIA PACIFIC FIBERS, TBK (Tahun 2016-2019) - Ismi Chairiah; Harold Hursepuny (P3M Politeknik Negeri Ambon, 2023)
The purpose of this study was to know the financial condition of PT. Asia Pacific Fibers, Tbk listed on the Indonesia Stock Exchanged 2016-2019 period. The study uses the method of Altman Z-Score. The company is expected to be able to take appropriate actions and policies after knowing the financial condition experienced by the company. This research is expected to provide information to the company as early as possible so that the company can take appropriate action to address the company's financial problems. This type of research is a case study using secondary data that comes from the financial statements of companies listed on the Indonesia Stock Exchange in 2016-2019. Based on the results of research showed in 2016-2019 PT. Asia Pacific Fibers, Tbk has great potential by going into bankruptcy. Keywords: Bankruptcy Analysis, Altman Z-Score